2009
DOI: 10.1007/s00401-009-0525-0
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic role of microRNAs in brain tumors

Abstract: MicroRNAs (miRNAs) are short non-protein-coding RNAs that function as key regulators of diverse biological processes through negative control on gene expression at the post-transcriptional level. Emerging evidence indicates that miRNAs play an important role in the development of human cancers, with their deregulation resulting in altered activity of downstream tumor suppressors, oncogenes and other signaling molecules. Recent years have seen considerable progress in miRNA research in brain tumors, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 90 publications
3
89
0
1
Order By: Relevance
“…Probing the miRNA milieu has already facilitated the discovery of many oncogenes (reviewed in ref. [119][120][121][122]. Similar studies with regards to HCV have revealed valuable knowledge with regards to host-virus interactions.…”
Section: 103mentioning
confidence: 90%
“…Probing the miRNA milieu has already facilitated the discovery of many oncogenes (reviewed in ref. [119][120][121][122]. Similar studies with regards to HCV have revealed valuable knowledge with regards to host-virus interactions.…”
Section: 103mentioning
confidence: 90%
“…[111] In MB, miR-21 suppression inhibited tumor migration. [112] MiR-183 has a pro-tumorigenic effect in the MYC-driven MB subgroup through the inhibition of apoptosis, deregulation of the mTOR pathway and modulation of cell motility and migration. [113] During the EMT process, malignant cells start to intravasate into the surrounding blood vessels in order to migrate to other parts of the body.…”
Section: Emt Cell Invasion and Motilitymentioning
confidence: 99%
“…Putative tumor suppressor miRNAs selected as candidates for Msi1 regulation includes miR-34a, miR-101, miR-128, miR-137 and miR-138. [30][31][32][33][34][35][36][37][38] A synopsis of their profiling studies, mRNA targets and impact on biological functions is summarized in Table 1. These miRNAs have decreased or no expression in brain tumors, as compared to normal brain tissue.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%